2018
DOI: 10.1155/2018/4961753
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Lymphocytes of Patients with Inflammatory Bowel Disease Have Altered Concentrations of Key Apoptosis Players: Preliminary Results

Abstract: Notwithstanding uncertain pathogenesis of inflammatory bowel disease (IBD), deregulation of adaptive immunity is paramount for the development of inflammation. Essential role in the resolution of inflammation is played by apoptosis, deregulated in lymphocytes isolated from inflamed intestine. Despite IBD being a systemic disease, little is known about apoptosis of peripheral lymphocytes. The concentrations of Bcl-2, cytochrome c, p53, and caspase-9 were determined (ELISA) in lymphocyte-enriched fractions of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…3). Our observations are consistent with the results obtained by Neubauer et al They assessed CASP-9 concentration in peripheral blood lymphocytes of patients with IBD by immunoenzyme method and showed signi cantly lower concentrations of CASP-9 in patients with active IBD compared to the control group (Neubauer et al 2018). A follow up study of our experiment was to determine CASP-9 mRNA expression in cell cultures of peripheral blood lymphocytes that were treated with IFX.…”
Section: Discussionsupporting
confidence: 92%
“…3). Our observations are consistent with the results obtained by Neubauer et al They assessed CASP-9 concentration in peripheral blood lymphocytes of patients with IBD by immunoenzyme method and showed signi cantly lower concentrations of CASP-9 in patients with active IBD compared to the control group (Neubauer et al 2018). A follow up study of our experiment was to determine CASP-9 mRNA expression in cell cultures of peripheral blood lymphocytes that were treated with IFX.…”
Section: Discussionsupporting
confidence: 92%
“…PCs are an important component of the intestinal epithelial barrier, so it is not surprising that functional abnormalities of PCs play a role in CD development[ 83 ]. The first pathological analysis of small intestine samples from CD patients revealed the presence of intracellular vesicle abnormalities in PCs in these patients[ 84 ].…”
Section: Paneth Cell Abnormalities and Microecological Disorders In Ibdmentioning
confidence: 99%
“…Both of these pathways also activate caspase, a protease that targets cellular proteins, triggering cell disassembly [ 20 ]. A previous study has revealed a decrease in intrinsic apoptosis in colitis compared to controls [ 21 ]. The role of apoptosis in colitis is also still controversial.…”
Section: Introductionmentioning
confidence: 99%